The Relationship Between Knowledge and Community Behavior In Efforts to Prevent Dengue Hemorrhagic Fever In The Sogaten Village Area, Manguharjo District, Madiun City In 2024 - Lisa Widya Astuti Suparno; Karina Nur R; Suhadi Prayitno (CV. Syntax Corporation Indonesia, 2024)
DHF is one of the national priorities for infectious disease control in Indonesia, every year the cases always increase and are increasingly widespread, causing extraordinary events (KLB). Therefore, the purpose of this study was to determine the relationship between knowledge, health promotion media and health worker support for the incidence of dengue hemorrhagic fever in Sogaten Village, Manguharjo District, Madiun City. This type of research is quantitative research, using a questionnaire sample of 24 respondents. Measuring instruments in this study used univariate and bivariate with the chi-square test. The results of the study on the knowledge variable using the Chi-square test resulted in an Asymp.Sig value. (2 tailed) = 0.012 with a significance level of 0.05. While the results of research on health promotion media variables using the Chi-square test with an Asymp.Sig value. (2tailed) = 0.036 with a significance level of 0.05. Meanwhile, the results of research on health worker support variables using the Chi-square test with an Asymp.Sig value. (2tailed) = 0.039 with a significance level of 0.05. The test criterion is that the H0 hypothesis is rejected if Asymp.Sig < 0.05. Because the Asymp.Sig results of knowledge, health promotion media and health worker support are smaller than 0.05, it means that H0 is rejected, so there is a relationship between the incidence of DHF and knowledge, health promotion media and health worker support to the community.